Glass formation and topology in relation to free volume, glass transition and band structure in Ge-Se-Sb chalcogenide system. (2023) - Kumar, Mahesh; Panda, Jayabrata; Sharda, Sunanda
Abstract: The algebraic criterion for glass formation and glass stability has been discussed in terms of the mechanical threshold and physical parameters like mean bond energy and lone pair electrons of the Ge20 Se80-x Sbx ( x  = 0, 4, 8, 12, 16, 20) chalcogenide system. The topological parameter, mean coordination number (< r  > ), has been correlated to the free volume percentage, glass transition temperature and theoretical bandgap of the system. Two approaches, namely, Manca's and Shimakawa's, have been used to calculate the theoretical bandgap. A stoichiometric composition at  x   = 16 has been predicted, and it is concluded that mechanical and chemical thresholds co-exist in the system and that the system is a potential candidate for IR applications.